2013
DOI: 10.1007/s00420-013-0895-4
|View full text |Cite
|
Sign up to set email alerts
|

Features of selenium metabolism in humans living under the conditions of North European Russia

Abstract: Over the course of 1 year, low levels of plasma selenium affect GP activity and thyroid hormone levels in humans living in North European Russia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
4
0
1
Order By: Relevance
“…Additionally, Parshukova et al [54] reported the effect of low levels of plasma selenium on GPx activity and thyroid hormone levels in humans living in northern European Russia. Thus, an imbalance in Se and/or I status of animals can result in altered activity of the main antioxidative enzymes, including those closely connected with Se metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Parshukova et al [54] reported the effect of low levels of plasma selenium on GPx activity and thyroid hormone levels in humans living in northern European Russia. Thus, an imbalance in Se and/or I status of animals can result in altered activity of the main antioxidative enzymes, including those closely connected with Se metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In this regards, Parshukova et al . [ 8 ] confirmed that low serum selenium levels have an effect on the thyroid hormone levels in North European Russia. Also, another study in China showed that higher plasma selenium was related to lower chance to be affected by hypothyroidism.…”
Section: Introductionmentioning
confidence: 94%
“…25 E em pacientes com diagnóstico de tireoidite de Hashimoto (TH) e doença de Graves (DG), baixos níveis séricos de selenoproteínas podem representar reações inflamatórias, com consequente aumento no consumo de proteínas dependentes de Se, na tentativa de prevenir a produção dos radicais livres gerados pela agressão autoimune tireoidiana. 24 Parshukova et al, 28 estudando as inter-relações entre níveis sazonais de Se e níveis de hormônios da tireoide ao longo de um ano, verificaram que níveis séricos baixos de Se afetavam os níveis dos hormônios tireoidianos. Além disso, Wu et al 29 realizaram um estudo em que se investigou a prevalência da doença tireoidiana em duas regiões semelhantes, exceto pela grande diferença nas concentrações de Se no solo.…”
Section: Gestantesunclassified